Poškodbe v slovenskem plesu - analiza in primerjava različnih plesnih zvrsti - Zaletel, Petra (Šport (Ljubljana), 2021)
Various dance techniques require control of the body in often extreme anatomical positions, which put a heavy strain on the musculoskeletal system, so the incidence of injuries in dance is increasing. The purpose of our study was to analyze the number and location of injuries in hip-hop, breakdance, standard and Latin American dances, and acrobatic rock and roll. The sample consisted of 247 male and female dancers, averaging 17.5 years of age. According to the location of the injury, most representatives of breakdance (91.18%) and acrobatic rock and roll (89%) were injured. More than half of breakdancers have an injured shoulder and knee, and just over 40% also have injured a wrist and spine. Over 40% of rock and roll dancers have an injured knee and ankle, similar to hip-hop (37% of the knee and 33% of the ankle). Representatives of standard and Latin American dances are generally the least injured, with over 20% of them have spinal and foot injuries. The average number of injuries per dancer is the highest in breakdanceg (15%), followed by hip-hop (3.38%) and rock and roll (2.83%). In the area of the hip, shin, ankle and foot, all dancers have a similar number of injuries. It will be necessary to design preventive training programs for the development of aerobic capacity and strength of dancers of various dance genres.
Keywords: breakdance; dance; hip hop; injuries; ples; poškodbe; rock and roll; rokenrol; sport; sport dance; šport; športni ples